Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 39 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Canthon quinquemaculatus Castelnau, 1840", "Geometry POLYGON((-88 -28,-88 9,-31 9,-31 -28,-88 -28))", "HasGeospatialIssue is false" ] } The dataset includes 39 records from 5 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000496-150422101436696/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences